The ubiquitin-proteasome pathway in cancer. - Spataro, V; Norbury, C; Harris, A (1998)
Degradation by the 26S proteasome of specific proteins that have been targeted by the ubiquitin pathway is the major intracellular non-lysosomal proteolytic mechanism and is involved in a broad range of processes, such as cell cycle progression, antigen presentation and control of gene expression. Recent work, reviewed here, has shown that this pathway is often the target of cancer-related deregulation and can underlie processes, such as oncogenic transformation, tumour progression, escape from immune surveillance and drug resistance.